Screening for unicellular algae as possible bioassay organisms for monitoring marine water samples. - Breiter, Roman; et al. (Water Research, 2006)
ECOTOX is an automatic early warning system to monitor potential pollution of freshwater, municipal or industrial waste waters or aquatic ecosystems. It is based on a real time image analysis of the motility and orientation parameters of the unicellular, photosynthetic flagellate Euglena gracilis. In order to widen the use of the device to marine habitats and saline waters nine marine flagellates were evaluated as putative bioassay organisms, viz. Dunaliella salina, Dunaliella viridis, Dunaliella bardawil, Prorocentrum minimum Kattegat, P. minimum Lissabon, Tetraselmis suecica, Heterocapsa triquetra, Gyrodinium dorsum and Cryptomonas maculata. Because of their slow growth the last three strains were excluded from further evaluation. Selection criteria were ease of culture, density of cell suspension, stability of motility and gravitactic orientation. The sensitivity toward toxins was tested using copper(II) ions. The instrument allows the user to automatically determine effect-concentration (EC) curves from which the EC(50) values can be calculated. For the interpretation of the EC curves a sigmoid logistic model was proposed which proved to be satisfactory for all tested strains. The inhibition of the motility was considered as the most appropriate movement parameter as an endpoint. The Dunaliella species had the lowest sensitivity to copper with EC(50) values of 220, 198 and 176 mg/L for D. salina, D. bardawil and D. viridis, respectively, followed by T. suecica with an EC(50) value of 40 mg/L. The Prorocentrum species were found to be the most sensitive with an EC(50) value of 13.5 mg/L for P. minimum Lissabon and 7.5 mg/L for P. minimum Kattegat.
Keywords: Copper toxicity; Dunaliella; ECOTOX; Marine flagellates; Prorocentrum; Tetraselmis